KEBIJAKAN PENGAWASAN PERBANKAN YANG INDEPENDEN DAN EFEKTIF MENURUT ARSITEKTUR PERBANKAN INDONESIA - Muhammad Pulung Aji Sukmo (Faculty of Social and Political Science, 2015)
This study discusses the independent and effectiveness by the Indonesian Banking Architecture (API) to the national banking system and before the establishment of the Financial Services Authority (FSA) oversight. The important role of national banks to the economy of Indonesia will impact on if something happens to the national banking system when its also had a significant effect on the national economy such as the crisis case in 1998 up to 2002 and 2008 before. It encourages the Government to create special institutions for which the duty to financial services supervision including banking sector. Through Law No. 21 of 2011 the government established the Financial Services Authority (FSA) is expected to be able to work independently and effectively perform their functions. This study officially made a compares The Act No. 21 of 2011 about Indonesian Banking Architecture (API) in supervision of national banks terms. Furthermore, this study reveal several factors inhibiting and supporting surveillance on Indonesian Banking Architecture (API) also. Hence, this research led the conclusion that the FSA can not be fully independent and effective as it should because there are still other agencies involved in the supervision of national banks and due to number of sectors that have to be monitored by FSA, in fact this kind of situation made the institution become very superior. Untill, the agency less focus oversee the national banking sector occur.